Association of late second trimester miscarriages with placental histology and autopsy findings. (December 2019) - Odendaal, Hein; Wright, Colleen; Brink, Lucy; Schubert, Pawel; Geldenhuys, Elaine; Groenewald, Coen
Abstract: Objectives: To describe the placental histology and autopsy findings in pregnancies where fetal demise occurred before a gestational age of 22 weeks. Study design: This study was a subset of a larger study where the effect of alcohol exposure during pregnancy on stillbirths was studied. In a prospective cohort, 7, 010 singleton pregnancies were followed from the first antenatal visit until infant one year of age visit. Gestational age was assessed by ultrasound, preferably at the first antenatal visit. All pregnancy losses were identified and when the fetuses delivered at or after a gestation of 20 weeks, the mother or parents were approached for consent for autopsy. This study describes the placental pathology and findings at autopsy in losses before 22 weeks gestation (late second trimester miscarriages). Results: Fourteen cases were identified in which 13 had an autopsy and 12 had a histological examination of the placenta. The most prevalent histological abnormality was placental abruption which was seen in 6 miscarriages, occasionally on its own, or in combination with maternal vascular malperfusion or acute chorioamnionitis. The second most frequent finding was maternal vascular malperfusion, as found in five placentas, alone or in combination with other pathology. The third most frequent pathology was acute chorioamnionitis, found in four placentas, in combination or alone. Other causes were diffuse chronic villitis due to cytomegalovirus infection and early amnion rupture with anhydramnios and cord obstruction. Conclusions: Causes of fetal demise at the end of the second trimester differ little from causes of stillbirth. There is value in using placental histology in late second trimester miscarriages to try to identify the cause of demise.